Marine Life Science & Technology - Song, Weibo; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer.)
Marine Life Science & Technology (MLST) provides a platform that introduces new discoveries and theories associated with marine organisms, bioresources, and biotechnology. The journal is intended for marine scientists, biological oceanographers, conservation biologists, marine technologists, policy makers and legislators. Accordingly, we will publish original research papers across a broad range of marine life sciences and technologies with an emphasis on synergistic interactions of multiple disciplines. Both theoretical and practical papers are welcome, including laboratory and field experimental studies relevant to marine life science and technology. We also encourage focused reviews, viewpoints, comments, and short communications. Moreover, as the journal$1 (Bs aim is to foster multidisciplinary approaches to marine sciences, authors will be encouraged to emphasise the relevance of their work in relation across our key-disciplines. Specifically, but not exclusively, MLST covers the following topics: Basic Biology: including biodiversity, development and evolution, genetics, reproductive biology, biochemistry, cell biology, omics and bioinformatics, epigenetics, stem cell biology, physiology and immunology, zoology, phycology, and microbiology. Fisheries Science: including marine fish biology, early life history, feeding and trophic dynamics, stock assessment, recruitment and reproduction, fisheries management, aquaculture engineering, stocking and enhancement technologies, aquatic breeding, aquafeeds, and aquatic disease. Marine Drugs and Bioproducts: including marine medicinal bioresources, bioactive natural products, pharmacology, lead compounds, drugs, and bioproducts. Food Science & Biological Technology: including the study of seafood nutrition; the theories and technologies associated with seafood processing and storage; seafood microbiology and associated issues. More widely, this topic covers marine biological technologies, including the development and application of marine bio-energy resources and marine-derived materials (e.g., antifouling agents, medical products, both aqua- and agricultural products). Finally, it can also include methods, novel equipment, and technologies associated with applied and ecological marine studies. Biological Oceanography: including marine plankton and benthic biology, microbial oceanology, fisheries oceanography, marine ecology, and food web dynamics.s
Keywords: Biodiversity; Aquatic ecology; Microbiology; Wildlife; Fish; Biology -- Technique; Freshwater & Marine Ecology; Fish & Wildlife Biology & Management; Biodiversity; Biological Techniques; Food Microbiology